A support interface method for easy part removal in directed energy deposition. (April 2019) - Jiang, Jingchao; Weng, Fei; Gao, Shiming; Stringer, Jonathan; Xu, Xun; Guo, Ping
Abstract: In traditional directed energy deposition (DED) processes, post-processing involving laser cutting or wire electrical discharge machining is necessary for removing printed parts from the substrate, which is time consuming and labor intensive. In this letter, a support interface method for DED is proposed for direct part removal without additional machining operations. A strut array is first printed as a sacrificial layer, upon which the actual part is then deposited. This letter demonstrates the method feasibility with a customized DED setup. It is expected that the proposed strategy will be beneficial in various DED processes to enhance process efficiency and automation.